2014
DOI: 10.1039/c4cp00746h
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of pentaglyme–sodium bis(trifluoromethanesulfonyl)amide solvate ionic liquid

Abstract: The physicochemical properties of pentaglyme (G5) and sodium bis(trifluoromethanesulfonyl)amide (Na[TFSA]) binary mixtures were investigated with respect to salt concentration and temperature. The density, viscosity, ionic conductivity, self-diffusion coefficient, and oxidative stability of a series of binary mixtures were measured, and the mixtures were examined as electrolytes for Na secondary batteries. An equimolar mixture of G5 and Na[TFSA] formed a low melting solvate, [Na(G5)1][TFSA], which exhibited an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 53 publications
10
82
1
1
Order By: Relevance
“…Here, we show examples of battery applications of Na‐based SILs. The [Na metal|[Na(G5)][TFSA]|Na 0.44 MnO 2 (SMO)] cell showed stable and reversible charge−discharge behavior at 60 °C, as shown in Figure a . This result indicates Na + ions are reversibly extracted/inserted from/into the MnO 2 framework.…”
Section: Structure and Properties Of Na K And Mg‐based Silsmentioning
confidence: 95%
See 1 more Smart Citation
“…Here, we show examples of battery applications of Na‐based SILs. The [Na metal|[Na(G5)][TFSA]|Na 0.44 MnO 2 (SMO)] cell showed stable and reversible charge−discharge behavior at 60 °C, as shown in Figure a . This result indicates Na + ions are reversibly extracted/inserted from/into the MnO 2 framework.…”
Section: Structure and Properties Of Na K And Mg‐based Silsmentioning
confidence: 95%
“…In addition to Li‐based SILs, non‐Li‐based SILs also show sufficient high thermal stabilities, negligible volatility, and non‐flammability with acceptable ionic conductivity ,. The electrochemical stabilities are also effectively enhanced upon complexation of glymes with metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…The use of glyme for the realization of “solvate ILs,” proposed for lithium system [ 117,118 ] has been also investigated for SIBs. Terada et al [ 119 ] investigated the physicochemical properties of tetraethylene glycol dimethyl ether (tetraglyme/TEGDME) and NaTFSI mixtures. The authors revealed the formation of a “solvate ILs” in which [Na(tetraglyme)] + cationic charge carriers are formed for equimolar ratio of NaTFSI:tetraglyme.…”
Section: Electrolytes For Na‐based Rechargeable Batteriesmentioning
confidence: 99%
“…It was observed that a weak Lewis‐acidic cation, such as the lithium–glyme complex, and a weak Lewis‐basic anion leads to ionic dissociation. They have also studied an equimolar mixture of pentaglyme (G5) and Na[NTf 2 ] in which the high ionicity suggested the solvate IL dissociates into the separate sodium glyme complex [Na(G5)] + cation and [NTf 2 ] − anion, despite the extremely high salt concentration in the liquid . Kar et al .…”
Section: Introductionmentioning
confidence: 99%
“…They have also studied an equimolar mixture of pentaglyme (G5) and Na[NTf 2 ]i n which the high ionicity suggested the solvate IL dissociates into the separates odium glyme complex [Na(G5)] + cation and [NTf 2 ] À anion, despite the extremely high salt concentration in the liquid. [26] Kar et al [27][28] made as imilar observation where an ovel quaternary alkoxy bis(trifluoromethylsulfonyl)amide [NTf 2 ]b ased IL with multiple oligo-ether side chains was demonstrated to interact and successfully solubilise zinc ions in an electrolyte proposed for aZn-air battery system.…”
Section: Introductionmentioning
confidence: 99%